Vitamin D status in recurrent aphthous stomatitis - Krawiecka, Ewa; Ślebioda, Zuzanna; Szponar, Elżbieta; Kowalska, Anna; Dorocka-Bobkowska, Barbara (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Recurrent aphthous stomatitis (RAS) is a common chronic inflammatory oral mucosa disease with an unknown cause. However, dysregulation of the immune response seems to play an important role in this disease. Aim : To evaluate the vitamin D status in RAS patients and its effects on RAS severity, given the likely immunomodulatory function of vitamin D in the human organism. Material and methods : Sixty-six patients with RAS and 66 controls were examined. Immunomodulatory or immunosuppressive treatment and other ulcerative oral diseases were used as exclusion criteria. The severity of RAS was assessed according to the clinical classification of the disease, the number of lesions per flare-up and the length of intervals between the attacks. The serum vitamin D level was established in each participant. Results : The mean serum vitamin D (25(OH)D) levels were found to be 16.81 ng/ml in the study group and 19.22 ng/ml in the control group, with no statistically significant difference between the two groups. In the study group, 5 (7.6%) participants were diagnosed with the “normal” vitamin D levels, while 16 (24.2%) had “insufficient” levels and 45 (68.2%) had “deficient” levels. The corresponding distribution in the control group was 8 (12.1%), 18 (27.3%) and 40 (60.6%), respectively. There was no statistical significance in the difference of vitamin D deficits between the study and the control groups. No correlation was detected between the severity of RAS and the serum vitamin D level. Conclusions : Vitamin D does not seem to be a trigger factor for RAS occurrence and does not appear to influence the severity of the disease in the studied group.